ANALISIS KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL MENGGUNAKAN TAKSONOMI STRUCTURE OF THE OBSERVED LEARNING OUTCOME - Putri, Renyka; Djudin, Tomo; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research aims to determine students’ competence in solving rotational dynamic problems using the Structure of the Observed Learning Outcome (SOLO) taxonomy. This research involved 102 of class XI science students of SMAN 1 Pontianak. The data was collected using a test in the form of four essay items; each item comprised four questions representing each level of SOLO taxonomy. The findings showed the average percentages of students’ competences in each the taxonomy level are 9.80% in pre-structural level (low category); 90.20% in uni-structural (high category); 72.30% in multi-structural level (medium category); 53.43% in relational level (medium category); and 22.55% in extended-abstract level (low category). There are differences in students’ competences in solving the problem at the uni-structural level observed from the high, medium, and low level of competence (0.000<0.05). The differences occurred between high and low groups (0.001<0.05) and between medium and low groups (0.001<0.05). Therefore, the overall competences in solving the problems using SOLO taxonomy was 49.66% (medium category). Further research is expected to bring improvement of the competences in solving the problems using the SOLO taxonomy. Keywords: Competence Level, Problem Solving Competence, SOLO Taxonomy